2013
DOI: 10.1186/2193-8865-3-67
|View full text |Cite
|
Sign up to set email alerts
|

Fruit-mediated synthesis of silver nanoparticles using Vitis vinifera and evaluation of their antimicrobial efficacy

Abstract: The present study reports an eco-friendly, biosynthesis of silver nanoparticles (AgNPs) using stem bark extract of Diospyros montana. Initially, the synthesis of AgNPs was confirmed by visual observation as color change. Further, the morphology of the biosynthesized nanoparticles, average size and presence of elemental silver were characterized by UV-Visible spectroscopy, scanning electron microscopy, transmission electron microscopy, energy dispersive X-ray and dynamic light scattering spectrometer. Qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
70
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(79 citation statements)
references
References 16 publications
9
70
0
Order By: Relevance
“…This result revealed that the formation of particles became complete after 4 h incubation time. Similar results have been reported by Chauhan et al [16] and Gnanajobitha et al [10].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This result revealed that the formation of particles became complete after 4 h incubation time. Similar results have been reported by Chauhan et al [16] and Gnanajobitha et al [10].…”
Section: Discussionsupporting
confidence: 82%
“…In line with this, green V. vinifera mediated AgNPs showed a characteristic absorbance peak at a wavelength of 449 nm by UV-visible spectroscopy. Behera and Nayak [9] and Gnanajobitha et al [10] reported that Indian black V. vinifera assisted AgNPs showed plasmon absorption band at 410 nm and around 450∼470 nm. It may have happened due to the species varieties of grapes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Additionally, resveratrol contains the Vitis vinifera fruit extract, used for the synthesis of AgNPs. [35][36][37] Therefore, we selected resveratrol as the reducing and stabilizing agent for the synthesis of AgNPs. To produce smaller-sized AgNPs, 5 mM AgNO 3 was added to 100 μM of resveratrol and incubated for 6 h at 40°C and pH 8.0.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The green synthesis approach usually employs microorganism or plant parts for the synthesis of nanoparticles. Recently, many researchers have employed different plant parts such as root, stem, bark, leaf, fruit, bud, and latex for the synthesis of AgNPs [7][8][9][10]. Reports have suggested that nanoparticles synthesized from medicinal plants have been found to be pharmacologically active and stable, but no hazardous by-products or toxic chemicals are used in their synthesis [11].…”
Section: Introductionmentioning
confidence: 99%